Validation of the in vivo Iodo-Nitro-Tetrazolium (INT) Salt Reduction Method as a Proxy for Plankton Respiration - García-Martín, E. Elena; Aranguren-Gassis, María; Karl, David M.; Martínez-García, Sandra; Robinson, Carol; Serret, Pablo; Teira, Eva (Frontiers in Marine Science, 2019)
Knowledge of the magnitude and variability of plankton respiration is a crucial gap in our understanding of marine carbon cycling. In order to validate the INT reduction method as a proxy for plankton respiration, we have compiled and analysed a dataset (n = 376) of concurrent measurements of dissolved oxygen consumption (CRO2) and in vivo reduction of 2-para (iodophenyl)-3(nitrophenyl)-5(phenyl) tetrazolium chloride tetrazolium salt (INT) spanning a wide range of oceanic regions and physicochemical conditions. Data were randomly divided into two independent subgroups: two thirds of the data were used to derive a regression conversion between dissolved oxygen consumption and INT reduction (“training” dataset) and one third of the data was used to validate the regression (“test” dataset). There was a significant relationship between the log-transformed dissolved oxygen consumption rates and the log-transformed INT reduction rates (INTT) with the “training” dataset (logCRO2 = 0.72logINTT + 0.44, R2 = 0.69, n = 249, p <0.001). The estimated oxygen consumption rates obtained applying the former equation were compared to the measured dissolved oxygen consumption rates from the “test” dataset which spans over three orders of magnitude range of respiration rates. There was no significant difference between the measured and estimated dissolved oxygen consumption rates, indicating that the INT reduction method can be used as a proxy for respiration in natural plankton communities. Further analysis dividing the data by temperature and chlorophyll-a concentration, indicated that the predictive capacity of the empirical conversion equation is increased at temperatures >8 ˚C and chlorophyll-a concentrations >0.2 µg L-1 and reduced at lower temperatures and chlorophyll-a concentrations. The results of this study endorse the adequate performance and reliability of the INT method for natural plankton communities.